REPRESENTASI GENDER DALAM TINDAK TUTUR ILOKUSI SELEBGRAM LOMBOK DI INSTAGRAM: KAJIAN PRAGMATIK DIGITAL - Wahyuni, Wika; Ramdhani, Marlinda; Susanti, Pipit Aprilia; Pratama, Januari Rizki (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research is motivated by the growing popularity of Instagram influencers (selebgram) in Indonesia, including in Lombok, who have now become role models and promotional media for various business sectors. The aim of this study is to analyze illocutionary speech acts, gender dominance, and the interests of the Lombok community as reflected in their engagement with selebgram content. Data were collected through observation and documentation, then analyzed using content analysis methods. The study reveals three main findings. First, selebgram in Lombok are predominantly female, with popular content focusing on fesyen, culinary arts, tourism, and entertainment. Second, female selebgram tend to use more commissive and expressive speech acts, while male selebgram are more inclined to use assertive and expressive forms. Third, Instagram audiences in Lombok show greater interest in following female selebgram and favor entertainment-related content. This study indicates that the popularity of selebgram in Lombok shapes communication patterns that reflect gender differences and, pragmatically, influence audience interests in the digital sphere. These findings highlight the importance of linguistic studies in understanding the role of selebgram as representations of popular culture and constructions of gender identity on social media.